Which Occupations Did People Engage in during Lockdown? A European Cross-Sectional Descriptive Survey by Generation - Cynthia Engels; Lauriane Segaux; Amandine Ibanez; Florence Canouï-Poitrine; Charlotte Lafont (Occupational Therapy International)
Objective. The primary objective was to describe the occupations people engaged in more frequently during lockdown than before the coronavirus disease 2019 pandemic as a function of generation. The secondary objectives were to (i) describe the levels of importance, performance, and satisfaction for these occupations and (ii) identify factors affecting the levels of importance, performance, and satisfaction. Method. We conducted an online, cross-sectional survey of young adults (YAs, aged 18-39), middle-aged adults (MAs, aged 40-59), and older adults (OAs, aged 60 or over). Results. 2534 participants (YAs: 47%, MAs: 33%, and OAs: 20%) cited 4500 occupations. The occupations in which people most engaged were leisure occupations (67%), followed by productive occupations (31%) and then self-care (2%) occupations. YAs gave a median (interquartile range) importance score of 8 (6; 9) to leisure, 8 (7; 10) to productivity, and 8 (7; 10) to self-care. MAs gave a median importance score of 8 (6; 10) to leisure, 8 (7; 10) to productivity, and 8 (7; 10) to self-care. OAs gave a median importance score of 8 (7; 10) to leisure, 8 (7; 9) to productivity, and 9 (8; 10) to self-care. In a pre-/postlockdown comparison, the changes in performance scores among YAs were +5 (3; 6) for leisure, +4 (2; 5) for productivity, and +4 (3; 6) for self-care. Among MAs, these changes were, respectively, +4 (3; 6), +3 (2; 5), and +4.5 (3; 6). Among OAs, these changes were, respectively, +3 (1; 5) for leisure, +3 (2; 5) for productivity, and +2 (0; 4) for self-care. The changes in satisfaction scores among YAs were +3 (0; 5) for leisure, +3 (0; 5) for productivity, and +3 (1; 6) for self-care. Among MAs, these changes were, respectively, +3 (0; 5), +2 (0; 4), and +5 (0; 6). Among OAs, these changes were, respectively, +2 (0; 4), +2 (0; 4), and +2 (0; 4). Conclusions. Lockdown led to stronger engagements in quiet leisure and alternative forms of socialization. Occupational therapists may have a role in helping community-dwelling people to balance and structure their new daily routine.